DISRUPTING AGING IN GERONTOLOGY: OLDER LATINAS ENGAGEMENT IN SOCIAL ACTIVISM. (16th November 2018) - Rodriguez, H
Abstract: The goal of this qualitative, study was to create and discover new knowledge on older Latinas and their lives as community activists. Currently, there is a lack of literature and research in gerontology that focuses on the experiences of older Latinas. Second, there is a lack of literature in the social sciences including gender studies and sociology that examines the activist roles Latinas have played in creating social change in society over their life course. This study examined the social role that older Latinas play in creating social change and in addressing social inequalities in their communities. Qualitative research methods in the form of interviewing were used to gather data from Latinas. Interviews were collected, transcribed, and coded using Atlasti. Coding of interviews was guided theoretically by the life course perspective and role-taking perspective in gerontology and sociology. Findings suggest that the activist experiences of older Latinas have a direct effect on their aging experience and quality of life. Findings from the study can be used to create future research-based programming for older Latinas that focus on social engagement, being engaged in the community, and becoming an advocate.